TEACHING LISTENING FOR SPECIFIC PURPOSES (BUSINESS, TRAVEL, ETC.) - Husinova Malika Matyoqub qizi Scientific advisor: Teshaboyeva Nafisa Zubaydulla qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
In today's diverse and dynamic world, the ability to understand spoken language in specific contexts is essential. Whether it's business, travel, medical settings, or any other professional field, Listening for Specific Purposes (LSP) has become a critical area of language learning. This article delves into LSP focuses on equipping learners with the skills they need to understand spoken language in particular situations or professional environments, helping them navigate real-world interactions more effectively.